Hubungan Pengetahuan dan Sikap terhadap Praktik Pencegahan COVID-19 pada Narapidana - Muhdar, Muhdar; Siagian, Heriviyatno Julika; Tulak, Grace Tedy; Baeda, Abd Gani; Tukatman, Tukatman; Mariany, Mariany (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2021)
Background: A prison or Detention Center is a closed community with a high risk of COVID-19 transmission. Preventive efforts to disseminate the virus are needed as soon as possible for the safety of assisted residents who have the possibility of conducting social distancing, considering that the number exceeds the ideal capacity of the detention centre. This study aimed to describe the knowledge, attitudes, and practices of assisted residents at Detention Center Class II B Kolaka regarding the COVID-19 Pandemic, which is very important as an evaluation of the condition of the inmates as a closed community and as a consideration for related parties for further local policymaking. Method: This was quantitative research using the cross-sectional design. There were 166 samples in Detention Center Class II B Kolaka. The instrument used was a questionnaire using 20 items. Data were analyzed using the chi-square test. Results: Out of 166 respondents, 92.8% had good knowledge, 87.3% had a confident attitude, 86.7% practised vigilance against the COVID-19 Pandemic. Based on the analysis using Chi-Square, it was found that p-value = 0.000, which means that there is a relationship between the level of knowledge and practice and between the respondent's attitude and practice.